2017
DOI: 10.1242/jcs.201350
|View full text |Cite
|
Sign up to set email alerts
|

Sequential activities of Dynein, Mud and Asp in centrosome–spindle coupling maintain centrosome number upon mitosis

Abstract: Centrosomes nucleate microtubules and are tightly coupled to the bipolar spindle to ensure genome integrity, cell division orientation and centrosome segregation. While the mechanisms of centrosome-dependent microtubule nucleation and bipolar spindle assembly have been the focus of numerous works, less is known about the mechanisms ensuring the centrosome-spindle coupling. The conserved NuMA protein (Mud in ) is best known for its role in spindle orientation. Here, we analyzed the role of Mud and two of its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…5a,c). Although recent work has shown that epithelial cells of asp mutants frequently exhibit supernumerary centrosomes [53], Asp depletion in S2 cells did not lead to an increase in the frequency of spindles associated with more than two centrosomes (Table 1). The latter finding is consistent with observations on brain cells from asp mutants [16], and suggests that the centrosomes of different cell types respond differently to Asp depletion.…”
Section: Resultsmentioning
confidence: 92%
“…5a,c). Although recent work has shown that epithelial cells of asp mutants frequently exhibit supernumerary centrosomes [53], Asp depletion in S2 cells did not lead to an increase in the frequency of spindles associated with more than two centrosomes (Table 1). The latter finding is consistent with observations on brain cells from asp mutants [16], and suggests that the centrosomes of different cell types respond differently to Asp depletion.…”
Section: Resultsmentioning
confidence: 92%
“…Depleting either Pins or Mud through RNAi increased planar spindles and relative D1+ cell numbers, suggesting that both proteins are required to orient oblique spindles ( Figures 4E, 5D, and S6G). Because Mud plays additional roles at the spindle pole during spindle assembly (Bosveld et al, 2017;Du et al, 2002;Izumi et al, 2006;Silk et al, 2009), we expressed GFPtagged Mud (using a Bac-based transgene in which GFP-tagged Mud is integrated at landing site 50E1, 62E1, and 65B2) (Bosveld et al, 2016) to visualize its localization and differentiate between the two functions of Mud. After inducing a regenerative response by Ecc15 treatment, we found that 55% of ISCs had Mud suggest that the activity of JNK promotes release of Mud from the cell cortex and thus prevents oblique spindles.…”
Section: Mud Is Sequestered From the Cortex In Stressed Iscsmentioning
confidence: 99%
“…The following stocks were used: koi 84 /Cyo-dfd-eYfp (FBst0025105) have been described previously (Kracklauer et al, 2007), koi-RNAi (FBst0040924), delta KASH (MSP-300 deltaKASH ;klar mCD4 /TM6B from J.A Fischer, University of Texas, Austin, TX), tubP-GAL80 ts /TM2 (FBst0007017), GAL4-Mef2.R (FBst0027390), , UAS-Spastin (obtained from V. Brodu, Institute Jacques Monod, Paris), ubi-H2B-mRFP/CyO; Dr/TM6B (Bosveld et al, 2017), UAS-klar-GFP (Elhanany-Tamir et al, 2012), Tub-Gal80ts; Mef2-Gal4 (obtained from F. Schnorrer IBDM, Marseille), UAS-2E12LI-EGFP(III)/TM6B (live H3K27me3-GFP mintbody obtained from H. Kimura, Tokyo Institute of Technology), His2Av-GFP (FBst0005941). Fly lines for Targeted Dam-ID (obtained from A.…”
Section: Methodsmentioning
confidence: 99%